Comparison of Arterial and Venous Interposition Grafting for Arterial Defects in a Rat Model - Sivakumar, Brahman; Thatcher, Keely; Hughes, Ian; Watson, Anna; Schick, Bernard; Graham, David J. (Journal of Reconstructive Microsurgery, 2023)
Background Interposition microvascular grafting may be required to bridge arterial defects during digital replantation or revascularization and has traditionally been performed utilizing a venous autograft. Arterial interposition grafting has been shown to be superior in maintaining patency in large vessel surgery; there are case reports of its use in microsurgery.Methods Six fellowship-trained hand and microsurgeons performed arterial and venous interposition grafts on the femoral arteries of 40 Wistar rats. After sectioning one femoral artery a segment of the contralateral femoral artery or vein was obtained. The time was recorded per graft and patency tested 10 minutes following grafting by an independent assessor. Each surgeon also completed a questionnaire detailing regular microsurgical volume, technical ease, and conceptual preference for either graft.Results Time for arterial interposition (median time 51.7 minutes) was longer than venous grafting (median time 45.9 minutes, p = 0.075). Arterial grafts were more likely to be patent or questionably patent (odds ratio [OR] = 6.77, p = 0.031). All surgeons found arterial interposition grafting technically easier and preferred it conceptually. Improvements were noted in patency rates (OR = 11.29, p = 0.018) and avoidance of anastomotic leak (OR = 0.19, p = 0.029) when surgeons performed moderate levels or greater of microsurgery within their regular practice.Conclusion Greater immediate patency was noted with arterial interposition grafting in a rodent model when compared to venous grafting, although procedural time was greater. All surgeons found arterial grafting technically easier. Arterial microvascular grafting may be useful in the setting of digital replantation or revascularization with an arterial defect.
Keywords: arterial repair; interposition grafting; microvascular grafting; revascularization; replantation; venous grafting